Efektivitas Fotokatalis Arang Untuk Mendegradasi COD, BOD, dan TSS Pada Limbah Tahu - Buka, Oktosea; Nurhaedah, Nurhaedah; Kurnia, Kurnia (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The presence of tofu waste compounds in water results in pollution that can contaminate biota. A more effective, efficient, easy and cheap organic waste processing technique for the tofu industry is using the photocatalyst method. Photocatalysis is a combination reaction between photochemistry and catalyst with shell charcoal as a catalyst. This research aims to determine the levels of COD, BOD, and TSS in tofu waste before and after photocatalysis, and to determine the effectiveness of charcoal photocatalysis to degrade tofu waste. In the SEM (Scanning Electrone Mycroscope) test results, it was identified that charcoal has a fairly large and loose pore surface. The test results for the water content were 2.4% and the ash content was 11.45% and the ash content did not meet the charcoal quality standards according to SNI 01-1682-1996, the water content was 6% and the ash content was 3%. The FTIR absorption test results that appear indicate the presence of the O-H group, the C-H Streching functional group, the C â‰¡ N Nitrile functional group (strong), the C=C aromatic ring functional group which is a form of hexagonal charcoal, the C-O functional group and the presence of the C-H aromatic ring functional group. Test results before and after photocatalysis on Tofu waste for COD levels of 122mg/l and >>> mg/l, BOD 3567 mg/l and 2071mg/l, TSS 138 mg/l and 18 mg/l. The effectiveness of charcoal photocatalysis to degrade tofu waste was effectively used for BOD test parameters with a reduction percentage of 41.9%, TSS of 86.9% and for COD test parameters it was not effective for the photocatalyst method.